2016
DOI: 10.1007/s11920-016-0723-0
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Post-Migration Stress and Psychological Disorders in Refugees and Asylum Seekers

Abstract: Refugees demonstrate high rates of post-traumatic stress disorder (PTSD) and other psychological disorders. The recent increase in forcible displacement internationally necessitates the understanding of factors associated with refugee mental health. While pre-migration trauma is recognized as a key predictor of mental health outcomes in refugees and asylum seekers, research has increasingly focused on the psychological effects of post-migration stressors in the settlement environment. This article reviews the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
480
3
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 520 publications
(533 citation statements)
references
References 72 publications
35
480
3
15
Order By: Relevance
“…At a glance, it would appear that the Afghans are reflecting on factors that can occur post-resettlement, which differs from the Iraqis, and offers insights into areas for future clinical focus such as developing culturally appropriate family-based therapies that take into account the change in the role of members of a refugee family unit. Our finding is also consistent with research which has previously demonstrated that the challenges of resettlement not only place increased demands on the refugee individuals themselves but also family units [31, 32]. …”
Section: Discussionsupporting
confidence: 92%
“…At a glance, it would appear that the Afghans are reflecting on factors that can occur post-resettlement, which differs from the Iraqis, and offers insights into areas for future clinical focus such as developing culturally appropriate family-based therapies that take into account the change in the role of members of a refugee family unit. Our finding is also consistent with research which has previously demonstrated that the challenges of resettlement not only place increased demands on the refugee individuals themselves but also family units [31, 32]. …”
Section: Discussionsupporting
confidence: 92%
“…It is widely acknowledged that post-migration factors are important determinants of mental health outcomes in resettled adult refugee samples [14]. These can be as powerful as, or even more so, than pre-migration experiences of war-related trauma and loss in predicting mental health outcomes [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, according to a review of 113 out of 840 studies on refugees' mental health, published from 1998 to 2009, including ten systematic reviews and five meta-analyses, traumas/stressors associated with migration that contributed to refugees' poor mental health status included famine, war, religious or political prosecution, disruption of social support and network, harsh living conditions in refugee camps, exposure to violence, uncertainty about future, discrimination and social exclusion, culture and language barriers, and economic distress [2]. As the number of refugees worldwide is rapidly growing, recent literature has re-emphasized the contribution of these traumatic experiences among refugee adults, adolescences, and children resettled in different countries to their mental well-being [7][8][9][10][11]. Abou-Saleh and Hughes [7], in their article, titled "Mental health of Syrian refugees: looking backwards and forwards," suggested that future effort to improve refugees' mental health should focus on "mental health and psychosocial support services that go beyond clinical services and include efforts to strengthen community support mechanisms and nonclinical interventions to strengthen coping mechanisms.…”
Section: Introductionmentioning
confidence: 99%